Steering the craft : a twenty-first century guide to sailing the sea of story - Le Guin, Ursula K., 1929-2018 (Mariner Books, 2015)
Presents advice on the basic elements of narrative prose, covering point of view, sentence length and complex syntax, indirect narration, grammar, punctuation, and the sound of writing.